Case Report: Infection with Streptococcus constellatus manifesting as gelatinous pleural effusion in an HIV-positive patient - Zhongxia Yang; Zhongxia Yang; Wanyuan Xiong; Wanyuan Xiong; Zibing Qian; Zibing Qian; Xiaorong Mao; Xiaorong Mao (Frontiers in Immunology)
Streptococcus constellatus, recognized as a commensal bacterium, has the potential to induce severe infections in patients with immunodeficiency. Here, we reported a rare case of Streptococcus constellatus infection that manifested as gelatinous pleural effusion in a patient with HIV. Although the effusion was gelatinous and partially encapsulated, it was completely resolved with timely administration of antibiotics, thereby eliminating the necessity for thoracic drainage, urokinase injection, or surgical intervention.